2016
DOI: 10.1186/s40249-016-0168-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of intestinal parasitism among two indigenous sub-ethnic groups in Peninsular Malaysia

Abstract: BackgroundIntestinal parasitic infections (IPIs) among indigenous people have been widely documented in Malaysia, however, the prevalence of these infections remains high. In the past, most studies have focused on specific species of parasites but polyparasitism has received limited attention. In addition, epidemiology studies on indigenous people tend to consider them as a homogenous group, whereas in reality different sub-ethnic groups have different cultural and living practices. Variations in living habits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 38 publications
1
31
2
2
Order By: Relevance
“…One would, on the contrary, expect the hot-spots to occur mainly within the northern parts of Ghana where the socioeconomically less privilege are mostly found. This finding is an unexpected departure from other previous studies 20 , 45 47 , and suggests that interaction effects of environmental and socioeconomic risk factors that combine best to enhance infection could play a role. Although the study did not build a formal causal explanation model for the clustering patterns, a visual comparison of the patterns with the ecological zones of Ghana generates a working hypothesis that is worth testing in future research efforts.…”
Section: Discussioncontrasting
confidence: 92%
“…One would, on the contrary, expect the hot-spots to occur mainly within the northern parts of Ghana where the socioeconomically less privilege are mostly found. This finding is an unexpected departure from other previous studies 20 , 45 47 , and suggests that interaction effects of environmental and socioeconomic risk factors that combine best to enhance infection could play a role. Although the study did not build a formal causal explanation model for the clustering patterns, a visual comparison of the patterns with the ecological zones of Ghana generates a working hypothesis that is worth testing in future research efforts.…”
Section: Discussioncontrasting
confidence: 92%
“…In addition, we did not observe any association between “supplied with piped water” and Cryptosporidium infection. Previous studies revealed that tap water was a risk factor for Cryptosporidium infection in other regions [ 25 , 30 ]. In our study, supplied drinking water covered most of the households.…”
Section: Discussionmentioning
confidence: 99%
“…This study found only four students (three males and one female) with mixed parasitic infections. The varying differences in mixed infections may be due differences in concentrations of parasites and sanitation conditions of the communities [ 20 ].…”
Section: Discussionmentioning
confidence: 99%